The role of aggression‐related early maladaptive schemas and schema modes in aggression in a prisoner sample. Issue 3 (25th January 2018) - Dunne, Ashley L.; Gilbert, Flora; Lee, Stuart; Daffern, Michael
Abstract : Contemporary social‐cognitive aggression theory and extant empirical research highlights the relationship between certain Early Maladaptive Schemas (EMSs) and aggression in offenders. To date, the related construct of schema modes, which presents a comprehensive and integrated schema unit, has received scant empirical attention. Furthermore, EMSs and schema modes have yet to be examined concurrently with respect to aggressive behavior. This study examined associations between EMSs, schema modes, and aggression in an offender sample. Two hundred and eight adult male prisoners completed self‐report psychological tests measuring their histories of aggression, EMSs, and schema modes. Regression analyses revealed that EMSs were significantly associated with aggression but did not account for a unique portion of variance once the effects of schema modes were taken into account. Three schema modes, Enraged Child, Impulsive Child, and Bully and Attack, significantly predicted aggression. These findings support the proposition that schema modes characterized by escalating states of anger, rage, and impulsivity characterize aggressive offenders. In this regard, we call attention to the need to include schema modes in contemporary social‐cognitive aggression theories, and suggest that systematic assessment and treatment of schema modes has the potential to enhance outcomes with violent offenders.